DEVELOPING STUDENT WORKSHEET OF ECOLOGYBASED DESCRIPTIVE TEXT WRITING IN SEVENTH GRADE OF MTS MUQIMUS SUNNAH PALEMBANG - Rizka Sukowati; Subadiyono Subadiyono; Suhardi Mukmin (Sriwijaya University Learning and Education International Conference, 2018)
This study aimed to produce teaching materials in the form of worksheet writing descriptive text based on ecology that could be used by students and teachers in class VII MTs Muqimus Sunnah Palembang.This study was a research and development (Collaboration Development) which collaborated to Jolly and Bolitho development model and development model of Dick, Carey, and Carey into eight steps, were: (1) identification of the need for teaching materials, (2) exploration of material needs, (3) contextual realization, (4) realization of pedagogics, (5) expert review, (7) revising learning, and (8) designing and conducting formative evaluations. The worksheet prototype of development outcomes consisted of: front cover, introduction, table of contents, study instructions, title, basic competencies, indicators, learning objectives, materials, tasks, exercises, assessment rubrics, and bibliography. To know the validity, practicality, and potential effects of worksheet developed, validation test by expert/expert and three stages of formative evaluation using questionnaire (questionnaire), interview, and test. Based on the validation of three aspects (the content of the substance of content/material, language, presentation, and graphic), worksheet was categorized as a very good or very valid. Based on the practicality test through on-one evaluation (onetooneevaluation) and group testing (smallgroup), worksheet was categorized as very good or very practical. From the field test results (fieldtest) through pretest and posttest, there was an average increase in the learner value of 17.95 so that LKPD could be categorized as effective or have potential effects for learners.